Pengaruh Teknologi 5G pada Evolusi Komunikasi: Sebuah Kajian Terhadap Perkembangan dan Implikasinya di Bidang Sains - Sugiyatno, Sugiyatno; Sidiq, Purnomo; Edrisy, Ibrahim Fikma (NUCLEUS, 2023)
The 5G technology represents a pivotal point in the evolution of communication and science, promising significantly enhanced speed, capacity, and reduced latency compared to previous generations. This study explores the transformative potential of 5G across various sectors, particularly in supporting scientific innovation through the Internet of Things (IoT), artificial intelligence (AI), and big data analytics. With the capability to accelerate experiments and simulations across diverse scientific fields, as well as facilitate remote scientific collaboration, 5G is expected to expedite innovation and scientific discoveries. However, the study also identifies challenges faced in the implementation and adoption of 5G, including data security issues, the need for substantial infrastructure investment, and potential health and environmental concerns. The study suggests an interdisciplinary approach in research to address these challenges and maximize the use of 5G technology. Additionally, emphasis on reducing energy use and adopting renewable energy sources indicates the need for more environmentally friendly communication. In conclusion, 5G has the potential to revolutionize the fields of science and technology, yet its success depends on cross-sector collaboration and the development of comprehensive strategies to overcome existing challenges.